Risk behaviours and self rated health in Russia 1998. Issue 11 (1st November 2001) - Carlson, P
Abstract : OBJECTIVES: As self rated health and mortality represent different dimensions of public health and as risk behaviours have been closely related to mortality, we wanted to examine whether (poor) self rated health on the one hand and risk behaviours on the other can be attributed to different causes. METHODS: The Taganrog household survey (1998) was conducted in the form of face to face interviews and included 1009 people and their families. To estimate health differences and differences in risk behaviours between groups, logistic regressions were performed. RESULTS: In Taganrog between 1993/94 and 1998, changes in self rated health seem to have been much more dramatic than changes in smoking and different in direction from changes in heavy alcohol consumption. Moreover, self rated "poor" health was especially common among those whose economic situation was worse in 1998 than 10 years before. However, having a poorer economy during the period 1988–1998, does not seem to have affected drinking or smoking habits significantly. CONCLUSIONS: Self rated health seems to be closely related to three indicators of economic circumstances. Risk behaviours are probably important for the poor state of public health in Russia, but may be less sensitive to the economic aspects of the transition than is self rated health.